HUBUNGAN KECERDASAN EMOSI GURU DALAM MENGAJAR DENGAN KEMAMPUAN SISWA DALAM MENERIMA PELAJARAN DI SMP TAMANSISWA PADANG - Sari, Windi - (Bimbingan dan Konseling, 2014)
This research motivated by the teacher scolded the students in learning, as well as the teacherwho hit the table at the time of hour lessons, the teacher who was teaching the words out that are lesscourteous to students, and the persistence of corporal punishment such as pinching students, studentsdespise storm at the time of study time, the lack of concentration of students in learning, when the dailyreset is still found in the student scores below a minimum completeness criteria (KKM). The purpose ofthis study describe: 1) emotional intelligence of teachers in classroom management, 2) the ability ofstudents to receive lessons, 3) Seeing teachers in teaching emotional relationship with a students abilityto absorb the lessons. This type of research is descriptive quantitative research. With a population of 175students. Sample size was 117 people. With the technique of sampling simple random sampling. Theinstrument used for data collection in the form of a questionnaire, the data used for the analysis of personproduct moment correlation method. The results of research show that: the emotional intelligence ofteachers in classroom management quite well when learning takes place in the management of teachersemotions in teaching, as well as the students ability to receive a lesson in class, and there is a relationshipbetween emotional intelligence of teachers in teaching with students ability to receive lessons in juniorTamansiswa Padang, the correlation obtained with r_hitung 0.737> 0.213 r_tabel with a significance levelof 0.01 <0.05 so that it can be interpreted "there is a relationship between emotional intelligence ofteachers in teaching with students ability to receive lessons in junior Tamansiswa Padang". It can also beseen from the mean or average of the respondents answer is 205.79.